0
$\begingroup$

This was a past year paper question. Not sure how to answer it.

Question: The 1-D discrete cosine transform(DCT) of a sequence f(x), x =0,1,...,N-1 is

F(u) = c(u)* Summation of f(x) cos ( (2x+1)u*pi/2N)

show that 1-D DCT of the sequence

g(x) = f(N-1-x), x = 0,1,...,N-1

can be expressed as G(u) = (-1)*F(u), u=0,1..., N-1

My solution (If wrong please correct me)

G(u) = c(u)* Summation of f(N-1-x) cos ((2(N-1-x)+1)u*pi/2N) = c(u)* Summation of f(N-1-x) cos (2N-2x-1)u*pi/2N)

$\endgroup$
  • $\begingroup$ This one should be pretty simple. Try substituting $F(N-1-x)$ into the given formula for the DCT and manipulate the expression algebraically to see if you can pull out a $(-1)$ factor. It's easier than you think. $\endgroup$ – Jason R Nov 15 '11 at 12:37
  • $\begingroup$ i will paste my solution below my question. If wrong please correct me.... $\endgroup$ – cnn lakshmen Nov 15 '11 at 12:44
  • $\begingroup$ not really sure brother need your help... $\endgroup$ – cnn lakshmen Nov 15 '11 at 13:07
4
$\begingroup$

If $g(x)= f(N-1-x)$ then $$\begin{aligned} (\operatorname{DCT}\:g)(u) =& c(u)\cdot\sum_{x=0}^{N-1}g(x)\cdot\cos\bigl((2x+1)u\cdot\tfrac\pi{2N}\bigr) \\=& c(u)\cdot\sum_{x=0}^{N-1}f(N-1-x) \cdot\cos\bigl((2N-2N+1+2x)u\cdot\tfrac\pi{2N}\bigr) \\=& c(u)\cdot\sum_{(N-1-x)=(N-1)}^{0}f(N-1-x) \cdot\cos\Bigl(\bigl(2N-1-2(N-1-x)\bigr)u\cdot\tfrac\pi{2N}\Bigr) \end{aligned}$$ substitute now $N-1-x=:\xi$, $$\begin{aligned} (\operatorname{DCT}\:g)(u) =& c(u)\cdot\sum_{\xi=0}^{N-1}f(\xi) \cdot\cos\Bigl(\bigl(2N-1-2\xi\bigr)u\cdot\tfrac\pi{2N}\Bigr) \\=& c(u)\cdot\sum_{\xi=0}^{N-1}f(\xi) \cdot\cos\Bigl(\pi\bigl(\tfrac{2N}{2N}-\tfrac{2\xi+1}{2N}\bigr)u\Bigr). \end{aligned}$$ In the cosine, we have now a shift by an integer multiple ($u$) of $\pi$. Such a shift in a sine or cosine function is equivalent to multiplying the function with $(-1)^u$, So the result is $$\begin{aligned} (\operatorname{DCT}\:g)(u) =& c(u)\cdot\sum_{\xi=0}^{N-1}f(\xi) \cdot\cos\bigl(\pi\tfrac{2\xi+1}{2N}u\bigr)\cdot(-1)^u \\=& (-1)^u\cdot(\operatorname{DCT}\:f)(u). \end{aligned}$$ Not quite the expression you wanted to show, but this should be the correct one.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.